Cognitive Impairment, Neuroimaging, and Alzheimer Neuropathology in Mouse Models of Down Syndrome - Hamlett, Eric D. (Curr Alzheimer Res, 2016)
Down syndrome (DS) is the most common non-lethal genetic condition that affects approximately 1 in 700 births in the United States of America. DS is characterized by complete or segmental chromosome 21 trisomy, which leads to variable intellectual disabilities, progressive memory loss, and accelerated neurodegeneration with age. During the last three decades, people with DS have experienced a doubling of life expectancy due to progress in treatment of medical comorbidities, which has allowed this population to reach the age when they develop early onset Alzheimer’s disease (AD). Individuals with DS develop cognitive and pathological hallmarks of AD in their fourth or fifth decade, and are currently lacking successful prevention or treatment options for dementia. The profound memory deficits associated with DS-related AD (DS-AD) have been associated with degeneration of several neuronal populations, but mechanisms of neurodegeneration are largely unexplored. The most successful animal model for DS is the Ts65Dn mouse, but several new models have also been developed. In the current review, we discuss recent findings and potential treatment options for the management of memory loss and AD neuropathology in DS mouse models. We also review age-related neuropathology, and recent findings from neuroimaging studies. The validation of appropriate DS mouse models that mimic neurodegeneration and memory loss in humans with DS can be valuable in the study of novel preventative and treatment interventions, and may be helpful in pinpointing gene-gene interactions as well as specific gene segments involved in neurodegeneration.